Phubbing Terhadap Kualitas Kelekatan Dewasa pada Perempuan Menikah di Kota Makassar - Sitti Murdiana; Ismalandari Ismail (Universitas Negeri Makassar, 2022)
This study aims to determine relationship between phubbing and adult attachment. This research was conducted on 72 married women spread across the city of Makassar using simple regression analysis methods in processing the data results. The results revealed that phubbing behavior influenced anxiety attachment and avoidance attachment. The effect of phubbing on anxious attachment appears to be less strong, but the effect of phubbing on attachment avoidance appears to be stronger. Based on these results, it can be concluded that phubbing affects adult attachment on the anxious aspect and on the avoidance aspect with a different magnitude of influence